The nuclear calcium signaling target, activating transcription factor 3 (ATF3), protects against dendrotoxicity and facilitates the recovery of synaptic transmission after an excitotoxic insult - Ahlgren, Hanna Henrika; Bas Orth, Carlos; Freitag, H. Eckehard; Hellwig, Andrea; Ottersen, Ole Petter; Bading, Hilmar (The journal of biological chemistry, 2014)
The focal swellings of dendrites (“dendritic beading”) are an early morphological hallmark of neuronal injury and dendrotoxicity. They are associated with a variety of pathological conditions, including brain ischemia, and cause an acute disruption of synaptic transmission and neuronal network function, which contribute to subsequent neuronal death. Here, we show that increased synaptic activity prior to excitotoxic injury protects, in a transcription-dependent manner, against dendritic beading. Expression of activating transcription factor 3 (ATF3), a nuclear calcium-regulated gene and member of the core gene program for acquired neuroprotection, can protect against dendritic beading. Conversely, knockdown of ATF3 exacerbates dendritic beading. Assessment of neuronal network functions using microelectrode array recordings revealed that hippocampal neurons expressing ATF3 were able to regain their ability for functional synaptic transmission and to participate in coherent neuronal network activity within 48 h after exposure to toxic concentrations of NMDA. Thus, in addition to attenuating cell death, synaptic activity and expression of ATF3 render hippocampal neurons more resistant to acute dendrotoxicity and loss of synapses. Dendroprotection can enhance recovery of neuronal network functions after excitotoxic insults.
Gesehen am 04.09.2020